ANALISIS STRATEGI PENGEMBANGAN BISNIS DILIHAT DARI FAKTOR INTERNAL DAN EKSTERNAL PADA USAHA YOLANDA CATERING ARGAMAKMUR - Anggun Witriani; Sri Ekowati (UM. Bengkulu, 2022)
This study aims to determine the analysis of business development strategies from internal and external factors at Yolanda Catering Argamakmur business. This research was a field research with a qualitative descriptive approach. The informants of reseach were managers, employees, and consumers of Yolanda Catering. The results showed that the internal factors core was 3.43; the score was up the score of 4.0, which illustrated Yolanda Catering's position in strong position. Moreover, the score for external factors was 3.00. This score was almost close to a score of 4.0, this means that Yolanda Catering takes advantage of existing opportunities and is able to avoid existing threats. If viewed based on the IE matrix, the score of internal and external factors was in cell1, which indicated Yolanda Catering is carrying out a growth strategy, which its the growth of the Printing itself, through vertical integration, an activity expanded the Catering market by maximizing promotions and development at other location points. From the SWOT matrix, Yolanda Catering is on the SO Strategy, which can take advantage of all strengths to seize and take advantages of opportunities as possible. The strategy applied in this condition to support an aggressive growth policy (Growth Oriented Strategy), this can continue the growth and expanse to achieve maximum Catering progress. This way does to maintain its extension in the midst of business competition to use the power of it and overcome external threats. Yolanda Catering provides good service so that consumers were satisfied with the performance of Yolanda Catering and add bonuses to consumers who always subscribe to Yolanda Catering, they do not turn to other catering products. Furthermore, Yolanda Catering attempted to follow the times or trends where other catering businesses promotions through newspapers, advertisements, magazines and social media. Its he results of the promotion were not widely, only around Argamakmur RegencyyÂ Keywords: business, development, promotion, catering, Yolanda.Â